Analytical abstracts a monthly journal dealing with all branches of analytical chemistry (Cambridge, Society for Analytical Chemistry, 1954-1973)
Analytical Abstracts is a current awareness and information retrieval service for analytical chemistry, published by the Royal Society of Chemistry in Cambridge, United Kingdom. It was first published in the mid-1950s by the Society for Analytical Chemistry which merged with other societies in 1980 to form the Royal Society of Chemistry. Analytical Abstracts is currently available online only. It used to be published in print edition on a monthly basis. The online version of the database is accessible to those who have access to Analytical Abstracts via an institutional licence. The online database is updated on a weekly basis, and users are able to sign up to receive email notifications informing them when an update has been submitted.